Pandemic, power and information technologies - de Vittorio, Luca (Revista Ethika+, 2020)
In this article it is sought to expose the relation between the current confinement situation with Internet and the multiple consequences massified data production can have in various ambits of our social experience. This entail the problematization of the status that Internet have in our daily life, how its architecture allows to articulate it as a power device and surveillance, in which measure operates as a unlimited source of various kinds of information and the possible consequences that this extraction have in both political and economic dimensions in our contemporary society.